Experimental anxiety and the reinforcing effects of ethanol in rats - Blatt,S.L. (1999)
In order to examine the relationship between anxiety and reinforcing effects of alcohol, drug-naive male Wistar rats weighing 250-300 g were classified as "anxious" and "non-anxious" in the elevated plus-maze test. A conditioned place preference test was then used to investigate the reinforcing effects of ethanol (EtOH) on these animals. On 2 alternate days, groups of "anxious", "non-anxious" and "normal" rats received intraperitoneal (ip) injections of EtOH (0.5, 1.0 or 1.5 g/kg) immediately before a 15-min confinement to the white compartment. On the 2 intervening days the same rats received ip injections of saline before confinement to the opposite compartment. On day 5, a 15-min free-choice test was carried out with no injections. Rats classified as "anxious" showed a significant, though not dose-dependent preference for all doses of ethanol compared to saline-treated animals. These data demonstrate that rats regarded as "anxious" are more sensitive to the reinforcing effects of EtOH than "non-anxious" and "normal" Wistar rats and emphasize the relevance of the basal levels of anxiety of rats when trying to detect the reinforcing effects of EtOH.